(untitled) (Global Journal of Science Frontier Research, 2018)
Mathematical science and Biological sciences are interdisciplinary approaches in the field of scientific research. Both of them deserve a wide range of applications. The study of mathematics for biology is sometimes called mathematical biology or biomathematics to stress the mathematical side, or theoretical biology to stress the biological side. One can derive the quantitative genetics through consideration of infinitesimal effects at a large number of gene loci, together with the assumption of linkage equilibrium or quasi-linkage equilibrium. Ronald Fisher made The intensive work on fundamental advances in statistics (Example: Analysis of Variance) belong to Ronald Fisher. This achievement by Ronald Fisher was through his work on quantitative genetics. The phylogenetics is one more important branch of population genetics that led to the extensive development of Biological sciences through Mathematics.